The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/bit.27458
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar mimics with periodic strain and its effect on the cell layer formation

Abstract: We report on the development of a new model of alveolar air-tissue interface on a chip. The model consists of an array of suspended hexagonal monolayers of gelatin nanofibers supported by microframes and a microfluidic device for the patch integration. The suspended monolayers are deformed to a central displacement of 40 -80 µm at the air-liquid interface by application of air pressure in the range of 200 -1000 Pa. With respect to the diameter of the monolayers that is 500 µm, this displacement corresponds to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…Using a similar platform, the same group further examined the influence of mechanical strain on alveolar epithelial wound healing [ 65 ]. Furthermore, instead of using conventional PDMS membrane, the same group developed a model of alveolar air–tissue interface on a chip consisting of an array of suspended hexagonal monolayers of nanofibers (made from gelatin or collagen + elastin) supported by microframes [ 66 , 67 ]. The membrane was integrated into a microfluidic device for the patch integration.…”
Section: Lung-on-a-chipmentioning
confidence: 99%
“…Using a similar platform, the same group further examined the influence of mechanical strain on alveolar epithelial wound healing [ 65 ]. Furthermore, instead of using conventional PDMS membrane, the same group developed a model of alveolar air–tissue interface on a chip consisting of an array of suspended hexagonal monolayers of nanofibers (made from gelatin or collagen + elastin) supported by microframes [ 66 , 67 ]. The membrane was integrated into a microfluidic device for the patch integration.…”
Section: Lung-on-a-chipmentioning
confidence: 99%
“…More recent studies have shown that membranes made of electrospun nanofibers or ECM hydrogels have a better biocompatibility and an improved mechanic property with respect to plastic or elastomeric membranes. [ 27–30 ] Yet, these membranes were not thin enough or made of synthetic polymers. Knowing that the natural BM made of type IV collagen and laminin is dense thin (≈100 nm thick), uniform, and highly permeable, it is important to recapitulate these essential features.…”
Section: Introductionmentioning
confidence: 99%
“…24 This approach offers the further benefit that properties such as fiber diameter, fiber orientation, porosity, mechanical strength, stretchability and thickness can be tailored to mimic the properties of the native ECM. 25 Electrospun membranes with fiber diameters in the micrometer range have previously been used to mimic the alveolar capillary basement membrane in macro-and microscale devices 11, 26, 27 However, only a few of these devices have incorporated basolateral media flow and these have been limited to macroscale devices. 28 Such macroscale devices are costly and take up considerable space, and are therefore limited with regard to how many replicates can be run in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Several different in vitro lung tissue models with cyclic mechanical stretch have been developed by integrating manufacturing techniques with cell culture. [5][6][7][8][9][10][11][12][13][14] Currently utilized models span from macro to microscale devices, the latter of which allow for complex devices to be manufactured with similar dimensions to the natural cell microenvironment. These devices have been used to study alveolar barrier function, 10,11,15 lung disease 13,16 , lung injury 7,14 and drug response 16,17 using lung on a chip devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation